2022
DOI: 10.4314/udslj.v17i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Odds

Abstract: This paper reports the findings of a qualitative study that has explored rural students’ experiences with online learning in Tanzania. The study used purposive sampling to select twenty-five participants. It employed a phenomenological design, primarily using semi-structured interviews coupled with document review, to obtain data on students’ lived experiences. The data was then subjected to thematic analysis to generate study findings which show that rural students used the Moodle system to support their onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…This is due to the fact that they did not receive feedback on time and they faced many technical challenges. The same concerns were reported in other studies by Semlambo et al (2022) and Mahai (2022) who revealed that instructors and students were unwilling to adopt online assessment due to technical, academic, poor access to the Internet, prohibitive costs of learning infrastructure, limited technical skills and security concerns. This is an indication that online assessment is likely to be affected by instructors' attitudes which does not provide adequate technical support to students which in turn compromises students' readiness for online assessment.…”
Section: Discussionsupporting
confidence: 70%
“…This is due to the fact that they did not receive feedback on time and they faced many technical challenges. The same concerns were reported in other studies by Semlambo et al (2022) and Mahai (2022) who revealed that instructors and students were unwilling to adopt online assessment due to technical, academic, poor access to the Internet, prohibitive costs of learning infrastructure, limited technical skills and security concerns. This is an indication that online assessment is likely to be affected by instructors' attitudes which does not provide adequate technical support to students which in turn compromises students' readiness for online assessment.…”
Section: Discussionsupporting
confidence: 70%